FORMATION OF THE MECHANISM OF MARKETING INVESTMENT SUPPORT FOR ENTERPRISES ON THE EXAMPLE OF IVANO-FRANKIVSK TERRITORIAL COMMUNITY - Благун, Іван (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2025)
The article examines the formation of a mechanism for marketing investment support for enterprises on the example of Ivano-Frankivsk territorial community. In the context of the crisis, decreasing demand for goods and services and increasing competition, territorial community enterprises need effective marketing strategies. This can be the key to success in attracting investment resources from both the state and private investors. The following scientific research methods were used in the study: analysis, synthesis, induction, deduction, and comparison. The study analyses the current state of enterprises. The sources of attracting investment in the enterprises of the territorial community are identified. The number of enterprises by economic sectors is analysed, and the volume of attracted investments is analysed in accordance with the sectors of the territorial community's economy. Based on the analysis, a mechanism for supporting marketing investments is developed and its impact on enterprises is determined in accordance with the sectors of the economy. These results of the study may allow the introduction of this mechanism for enterprises in other territorial communities in order to increase investment in enterprises. The possibility and specificity of implementing a mechanism for supporting marketing investments in accordance with each of the blocks of the mechanism have been outlined. The sources of financing of enterprises are analysed, which made it possible to understand that the investment activity of enterprises is based on internal investments. The most investment-attractive sector of the territorial community is construction. This may be due to the internal migration of people within the country. It has been identified that one of the key problems is the low involvement of individual entrepreneurs in marketing, which in turn leads to a decrease in the investment attractiveness of the territorial community, as individual entrepreneurs are part of the sectors of the economy that are the largest in the community. For large enterprises, investment in marketing can be a driver of development in terms of investment attractiveness both nationally and internationally, while for small enterprises and entrepreneurs, training should be provided to effectively use and invest in marketing tools. This includes digital marketing tools and CRM systems.